Calculation of the Magnetoresistance of YMn2Ge2 and LaMn2Ge2 - Milano, Julian (2000)
We have calculated the diffusive conductivity and ballistic conductance of the layered compounds LaMn2Ge2 and  YMn2Ge2 . For the last one we obtain a negative band contribution to the giant magnetoresistance. For LaMn2Ge2 we show that the band contribution can already explain the experimentally observed large positive magnetoresistance if a nearly ferromagnetic structure is considered.